2009
DOI: 10.3748/wjg.15.2651
|View full text |Cite
|
Sign up to set email alerts
|

Major complications after radiofrequency ablation for liver tumors: Analysis of 255 patients

Abstract: RFA can be accepted as a relatively safe procedure for the treatment of liver tumors. However, attention should be paid to possible complications even though the incidences of these complications are rare. Careful patient selection and the best approach choice (percutaneous, laparoscopy, or laparotomy) will help to minimize the incidence and morbidity rate of complications which occur after RFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 29 publications
3
68
0
1
Order By: Relevance
“…Mortality related to the procedure is low, reported in the literature to be less than 1% [7][8][9] . Tumor type, type of approach, number of lesions, tumor localization, underlying hepatic disease, the physician's experience, associated hepatic resection and lesion size have been described as factors significantly associated with complications [9][10][11][12] . In one of their papers, Poon et al [10] concluded that after the physician's first 50 procedures, the incidence of complications is lower, as well as a shorter hospital stay and higher complete ablation rate.…”
Section: Topic Highlightmentioning
confidence: 99%
See 3 more Smart Citations
“…Mortality related to the procedure is low, reported in the literature to be less than 1% [7][8][9] . Tumor type, type of approach, number of lesions, tumor localization, underlying hepatic disease, the physician's experience, associated hepatic resection and lesion size have been described as factors significantly associated with complications [9][10][11][12] . In one of their papers, Poon et al [10] concluded that after the physician's first 50 procedures, the incidence of complications is lower, as well as a shorter hospital stay and higher complete ablation rate.…”
Section: Topic Highlightmentioning
confidence: 99%
“…This group of complications consists of hepatic abscess, wound infection and sepsis. Hepatic abscess is a potentially dangerous complication with an incidence ranging in the literature from 0.3% to 1.7% [6,9,11,12,[21][22][23] . It can appear up to more than 60 d after the procedure [23] .…”
Section: Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear if this alteration also affects the efficacy of intra-arterial therapies. Additionally, liver reserve may be more tenuous in the setting of large hepatic ablations [5,6].…”
Section: Introductionmentioning
confidence: 99%